Optical properties of dysprosium monoantimonide thin films - Tabatadze, I.G.; Jabua, Z.U.; Gigineishvili, A.V. (Физическая инженерия поверхности, 2013)
A process has been developed for the growth of thin crystalline DySb films by thermal evaporation using Dy and Sb separate sourses. The room-temperature optical spectra (reflection and absorption, the real and the imaginary part of the dielectric constant, loss function) of DySb films have been studied at photon energies from 0.05 to 5.5 eV. The behavior and energy position of features in the spectra have been analyzed.